A New Weak Chelator in Endodontics: Effects of Different Irrigation Regimens with Etidronate on Root Dentin Microhardness - Talita Tartari; Patrícia de Almeida Rodrigues Silva e Souza; Bruno Vila Nova de Almeida; José Otávio Carrera Silva Júnior; Oscar Facíola Pessoa; Mario Honorato Silva e Souza Junior (Hindawi Limited, 2013)
This study investigated the effect of sodium hypochlorite (NaOCl), ethylenediaminetetraacetic (EDTA), etidronic (HEBP), and citric acid (CA) associated in different irrigation regimens on root dentin microhardness. Forty-five root halves of single-rooted teeth were sectioned into thirds that were embedded in acrylic resin, polished, randomly assigned into 3 groups, and treated as follows: G1: saline solution; G2: 5% NaOCl + 18% HEBP, mixed in equal parts; and G3: 2.5% NaOCl. After measurements, the G3 samples were distributed into subgroups G4, G5, and G6, which were submitted to 17% EDTA, 10% CA and 9% HEBP, respectively. Following the new measurements, these groups received a final flush with 2.5% NaOCl, producing G7, G8, and G9. Microhardness was measured with Knoop indenter under a 25 g load for 15 seconds, before and after treatments. The data were statistically analyzed using paired Student's t-test (α<0.05) to compare values before and after treatments and analysis of variance (ANOVA) (α<0.05) to detect any differences among thirds. Except G1, all tested irrigation regimens significantly decreased the microhardness. There were no differences between root thirds before treatments, and all root thirds exhibited equal responses to same treatment. Except saline, all tested irrigation regimens reduced the root dentin microhardness.